G-Quadruplexes Are Present in Human Coronaviruses Including SARS-CoV-2 - Cui, Haoran; Zhang, Leiliang (Frontiers in Microbiology, 2020)
The global coronavirus disease 2019 (COVID-19) pandemic is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is one of seven human coronaviruses. G-quadruplexes are intrinsic obstacles to genome replication. Whether G-quadruplexes are present in human coronaviruses is unknown. In the current study, we have predicted that all seven human coronaviruses harbor G-quadruplex sequences. Conserved G-quadruplex sequences in SARS-CoV and SARS-CoV-2 were analyzed and verified by circular dichroism (CD) spectroscopy and Thioflavin T fluorescence assay. Similar to SARS-CoV, SARS-CoV-2 encodes an nsP3 protein, which is predicted to associate with G-quadruplexes. Targeting G-quadruplex sequences in the SARS-CoV-2 genome by G-quadruplex ligands could be a new way to conquer COVID-19.